Developmental Patterning and Neurogenetic Gradients of Nurr1 Positive Neurons in the Rat Claustrum and Lateral Cortex - Fang, Chao; Wang, Hong; Naumann, Robert Konrad (Frontiers in Neuroanatomy, 2021)
The claustrum is an enigmatic brain structure thought to be important for conscious sensations. Recent studies have focused on gene expression patterns, connectivity, and function of the claustrum, but relatively little is known about its development. Interestingly, claustrum-enriched genes, including the previously identified marker Nurr1, are not only expressed in the classical claustrum complex, but also embedded within lateral neocortical regions in rodents. Recent studies suggest that Nurr1 positive neurons in the lateral cortex share a highly conserved genetic expression pattern with claustrum neurons. Thus, we focus on the developmental progression and birth dating pattern of the claustrum and Nurr1 positive neurons in the lateral cortex. We comprehensively investigate the expression of Nurr1 at various stages of development in the rat and find that Nurr1 expression first appears as an elongated line along the anterior-posterior axis on embryonic day 13.5 (E13.5), and then gradually differentiates into multiple sub-regions during prenatal development. Previous birth dating studies of the claustrum have led to conflicting results, therefore we combine 5-ethynyl-2’-deoxyuridine (EdU) labeling with in situ hybridization for Nurr1 to study birth dating patterns. We find that most dorsal endopiriform (DEn) neurons are born on E13.5 to E14.5. Ventral claustrum (vCL) and dorsal claustrum (dCL) are mainly born on E14.5 to E15.5. Nurr1 positive cortical deep layer neurons (dLn) and superficial layer neurons (sLn) are mainly born on E14.5 to E15.5 and E15.5 to E17.5, respectively. Finally, we identify ventral to dorsal and posterior to anterior neurogenetic gradients within vCL and DEn. Thus, our findings suggest that claustrum and Nurr1 positive neurons in the lateral cortex are born sequentially over several days of embryonic development and contribute towards charting the complex developmental pattern of the claustrum in rodents.